2010
DOI: 10.1149/1.3246839
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Blue-Emitting Ce[sub x]Si[sub 6−z]Al[sub z−x]O[sub z+1.5x]N[sub 8−z−x] for White Light-Emitting Diodes

Abstract: In this work, blue-emitting CexSi6−zAlz−xnormalOz+1.5xnormalN8−z−x (0.3≤z≤2.5,0.5≤x≤2.5) phosphors were synthesized by firing powder mixtures of α-Si3normalN4 , AlN, Al2normalO3 , and CeO2 at 1950°C for 2 h under 1.0 MPa normalN2 . The resultant phosphors were characterized by phase identification, diffuse reflectance spectra, photoluminescence spectra, quantum efficiency, and temperature-dependent luminescence. The samples showed high purity at the overall range of the varied x and z values. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(137 citation statements)
references
References 32 publications
8
127
2
Order By: Relevance
“…This can be assigned to the differences in the coordination polyhedra of the Ce 3 + ions in these compounds. Also note that the found value of E cfs (20,200 cm À 1 ) essentially differs from that (E cfs ¼11,400 cm -1 ) reported for Ce 3 + ions in Li 2 SrSiO 4 by Liu et al [13]. The most probable explanation is that Liu et al [13] have used a lamp source with a very low output at wavelengths shorter than 240 nm, so that the excitation bands at 209 and 218 nm were not recorded in their experiments.…”
Section: What Factors Cause the Long-wavelength Position Of The Eu 2 contrasting
confidence: 98%
See 3 more Smart Citations
“…This can be assigned to the differences in the coordination polyhedra of the Ce 3 + ions in these compounds. Also note that the found value of E cfs (20,200 cm À 1 ) essentially differs from that (E cfs ¼11,400 cm -1 ) reported for Ce 3 + ions in Li 2 SrSiO 4 by Liu et al [13]. The most probable explanation is that Liu et al [13] have used a lamp source with a very low output at wavelengths shorter than 240 nm, so that the excitation bands at 209 and 218 nm were not recorded in their experiments.…”
Section: What Factors Cause the Long-wavelength Position Of The Eu 2 contrasting
confidence: 98%
“…This differs from that (d¼2400 cm À 1 ) found in the present work. This discrepancy can be explained by the existence of several kinds of cerium centers in the sample studied by Liu et al [13]. As seen from Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Liu et al [106] have reported on the phosphor Li 2 Sr 1-3x/2 Ce x SiO 4 (x = 0.0025-0.07). The material was prepared by high temperature solid state synthesis as a single phase and it was found that Ce 3?…”
Section: Blue Phosphors-oxide Hosts: Phosphates Silicates Aluminatesmentioning
confidence: 99%